Review of the Synthesis and Degradation Mechanisms of Some Biodegradable Polymers in Natural Environments - Yao, Xiao; Yang, Xue; Lu, Yisang; Qiu, Yinyuan; Zeng, Qinda (Polymers, 2025)
The escalating demand for sustainable materials has been fueling the rapid proliferation of the biopolymer market. Biodegradable polymers within natural habitats predominantly undergo degradation mediated by microorganisms. These microorganisms secrete enzymes that cleave long-chain polymers into smaller fragments for metabolic assimilation. This review is centered around dissecting the degradation mechanisms of specific biodegradable polymers, namely PLA, starch-based polymers, and plant fiber-based polymers. Recent investigations have unveiled that PLA exhibits augmented biocompatibility when combined with HA, and its degradation is subject to the influence of enzymatic and abiotic determinants. In the case of starch-based polymers, chemical or physical modifications can modulate their degradation kinetics, as evidenced by Wang et al.’s superhydrophobic starch-based nanocomposite cryogel. For plant fiber-based polymers, the effects of temperature, humidity, and cellulose degradation on their properties, along with the implications of various treatments and additives, are probed, as exemplified by Liu et al.’s study on jute/SiO2/PP composites. Specifically, with respect to PLA, the polymerization process and the role of catalysts such as SnCl2 in governing the structure and biodegradability are expounded in detail. The degradation of PLA in SBF and its interaction with β-TCP particles constitute crucial aspects. For starch-based polymers, the enzymatic degradation catalyzed by amylase and glucosidase and the environmental impacts of temperature and humidity, in addition to the structural ramifications of amylose and amylopectin, are further elucidated. In plant fiber-based polymers, the biodegradation of cellulose and the effects of plasma treatment, electron beam irradiation, nanoparticles, and crosslinking agents on water resistance and stability are explicated with experimental substantiation. This manuscript also delineates technological accomplishments. PLA incorporated with HA demonstrates enhanced biocompatibility and finds utility in drug delivery systems. Starch-based polymers can be engineered for tailored degradation. Plant fiber-based polymers acquire water resistance and durability through specific treatments or the addition of nanoparticles, thereby widening their application spectrum. Synthetic and surface modification methodologies can be harnessed to optimize these materials. This paper also consolidates reaction conditions, research techniques, their merits, and demerits and delves into the biodegradation reaction mechanisms of these polymers. A comprehensive understanding of these degradation mechanisms is conducive to their application and progression in the context of sustainable development and environmental conservation.